2020
DOI: 10.3390/cells9030687
|View full text |Cite
|
Sign up to set email alerts
|

VEGF Triggers Transient Induction of Autophagy in Endothelial Cells via AMPKα1

Abstract: AMP-activated protein kinase (AMPK) is activated by vascular endothelial growth factor (VEGF) in endothelial cells and it is significantly involved in VEGF-induced angiogenesis. This study investigates whether the VEGF/AMPK pathway regulates autophagy in endothelial cells and whether this is linked to its pro-angiogenic role. We show that VEGF leads to AMPKα1-dependent phosphorylation of Unc-51-like kinase 1 (ULK1) at its serine residue 556 and to the subsequent phosphorylation of the ULK1 substrate ATG14. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 80 publications
0
29
0
Order By: Relevance
“…Growth of the vascular network is a highly dynamic process, comprising many individual steps promoting the dynamic shift between quiescence and proliferation and sprouting of ECs. Recent research demonstrated that vascular endothelial growth factor (VEGF) activates autophagic flux by an AMPK-dependent mechanism [33]. Notably, the activation of autophagy in response to VEGF is transient, and it is opposed by a delayed activation of mTOR by VEGF itself [33].…”
Section: Autophagy Controls Endothelial Cells Homeostasis and Functionsmentioning
confidence: 99%
“…Growth of the vascular network is a highly dynamic process, comprising many individual steps promoting the dynamic shift between quiescence and proliferation and sprouting of ECs. Recent research demonstrated that vascular endothelial growth factor (VEGF) activates autophagic flux by an AMPK-dependent mechanism [33]. Notably, the activation of autophagy in response to VEGF is transient, and it is opposed by a delayed activation of mTOR by VEGF itself [33].…”
Section: Autophagy Controls Endothelial Cells Homeostasis and Functionsmentioning
confidence: 99%
“…HUVEC were isolated from anonymously acquired human umbilical cords according to the "Ethical principles for Medical Research Involving Human Subjects" (Declaration of Helsinki 1964) as previously described (Spengler et al, 2020). The protocol was approved by the Jena University Hospital Ethics Committee.…”
Section: Huvec Cell Culture and Treatmentmentioning
confidence: 99%
“…For example, Chen et al found that VEGF promoted the occurrence of autophagy and VEGF knockdown decreased the autophagy level 39 . In addition, Spengler et al 40 discovered that VEGF signaling pathway regulated autophagy in endothelial cells. Taken together, we speculated that autophagy probably contributed to the occurrence and development of LUAD through VEGF signaling pathway, and that the ARlncRNA signature was closely associated with tumor immunity.…”
Section: Discussionmentioning
confidence: 99%